2017
DOI: 10.1111/1468-5973.12185
|View full text |Cite
|
Sign up to set email alerts
|

Mobile text alerts are an effective way of communicating emergency information to adolescents: Results from focus groups with 12‐ to 18‐year‐olds

Abstract: Mobile phone text messages can be used to disseminate information and advice to the public in disasters. We sought to identify factors influencing how adolescents would respond to receiving emergency text messages. Qualitative interviews were conducted with participants aged 12-18 years. Participants discussed scenarios relating to flooding and the discovery of an unexploded World War Two bomb and were shown example alerts that might be sent out in these circumstances. Intended compliance with the alerts was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
(45 reference statements)
3
23
0
Order By: Relevance
“…Although threats to credibility may result from a general lack of knowledge and confidence in WEA messages among the public (Kar et al, ), qualitative findings identify additional explanations for these patterns, including message style and phone number of the message source. Similar to other studies that have found elements of message style to contribute to credibility (Wong et al, ), participants described analysing the level of detail, formality of the language, and even punctuation to determine message credibility. Some research supports individuals were more inclined to believe in the message, and thus follow message instructions, when messages were from a recognizable source, such as a government agency, compared with informal sources (i.e., user‐generated social media) (Freberg, ; Wogalter, ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although threats to credibility may result from a general lack of knowledge and confidence in WEA messages among the public (Kar et al, ), qualitative findings identify additional explanations for these patterns, including message style and phone number of the message source. Similar to other studies that have found elements of message style to contribute to credibility (Wong et al, ), participants described analysing the level of detail, formality of the language, and even punctuation to determine message credibility. Some research supports individuals were more inclined to believe in the message, and thus follow message instructions, when messages were from a recognizable source, such as a government agency, compared with informal sources (i.e., user‐generated social media) (Freberg, ; Wogalter, ).…”
Section: Discussionmentioning
confidence: 83%
“…Participants also expressed being desensitized to emergency alert messages as they perceived too many previous alert messages to be irrelevant, hindering public trust of warning messages (Woody & Ellison, ). Desensitization to warning and alert messages was also cited to reduce the system's impact on behaviour in other recent studies (Baseman et al, ; Lee, Chung, & Kim, ; Perry, Pulley, Paugh, Mignot, & MacGregor‐Skinner, ; Wong et al, ). When an organization, like a university, provides training and information regularly, it may be unintentionally affecting the effect it has on its stakeholders when an actual emergency hits, where message recipients assume the messages are another drill and subsequently ignore the message (Stephens et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further, trust relationships are developed through strong bi‐directional communications that lead to gradual reduction in tension between citizens and authorities (Busà, Musacchio, Finan, & Fennel, ), though there is little research into whether such functions may also be ascribed to mobile phone apps that are specifically designed for disaster communication. For example, when studying the effectiveness of mobile text alerts in emergency situations, Wong and colleagues found that text messages sent out by a trusted source were seen by participating citizens to be not enough but need to be embedded in a system that allows bi‐directional communication (Wong, Jones, & Rubin, ). This finding confirmed earlier research conducted on citizens' perceptions of Wireless Emergency Alerts (WEA), where participants appreciated that in case of an emergency short messaging may be required, but they also felt frustration—or even uncertainty or fear—due to a lack of background information and the lack of an interactive option for validation or clarification (Bean et al, ), which can undermine or, at least, fail to support or create trust.…”
Section: “Disaster Apps” and Trust In Authoritiesmentioning
confidence: 99%
“…For example, ride-share apps such as Uber offer GPS tracking that can be shared with family and friends in real time, as well as a distress alarm available on the app that can signal the ride-sharing service for help (69). Increased safety through technology can also be in the form of delivering safety information, such as the use of mobile technology for delivery of safety awareness in the workplace (70) and communicating emergency safety information through mobile text alerts (71). Safety in relation to technology and sexualized violence, however, has primarily been discussed negatively.…”
Section: Discussionmentioning
confidence: 99%